Gambaran Pengetahuan dan Sikap Perawat Tentang Resusitasi Jantung Paru di Puskesmas Bontonompo II - Rido Firmansyah; Fanny Dewi Sartika; Andi Budiyanto (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2025)
Cardiopulmonary resuscitation is a series of victim- saving measures that increase the chances of survival after cardiac arrest. Nurses' knowledge about resuscitation is a very important asset for implementing resuscitation actions or attitudes in critical situations. To find out the description of the level of knowledge and attitudes of Bontonompo II Health Center nurses regarding cardiopulmonary resuscitation (CPR). This research design uses quantitative descriptive research methods. The results of the study showed that of the 35 respondents who had good knowledge about Cardiopulmonary Resuscitation (CPR), 32 respondents (91.3%), 2 respondents (8.5%) had a sufficient level of knowledge and 0 had a poor level of knowledge. respondents. And of the 35 respondents who had a good attitude about Cardiopulmonary Resuscitation (CPR), 32 respondents (91.4%) had a fair attitude, 3 respondents (8.5%), and 0 respondents (0) had a poor attitude. %). In this study it can be concluded that the majority of nurses have good knowledge and attitudes.